2020
DOI: 10.3389/fphar.2020.563967
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Vancomycin in Kidney Transplant Recipients: Model Building and Parameter Optimization

Abstract: Background: Depending on the renal function of patients and many other influencing factors, studies on vancomycin pharmacokinetics show significant inter-and intraindividual variability. The present study was conducted using a population pharmacokinetics method to investigate the pharmacokinetic parameters and identified their influencing covariates for intravenous vancomycin in adult kidney transplant recipients. Methods:The drug monitoring data included 56 adult renal transplant recipients who received intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“… 7 The estimated CL (2.02 L/h) was nearly identical to what is seen in other population studies. 19 , 22 , 23 The typical value of V (65 L) was comparable to previously reported values. 18 , 22 , 24 During the covariate selection process, the OFV value decreased by 50.22 points (p>0.001) when CLcr was added to the model.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“… 7 The estimated CL (2.02 L/h) was nearly identical to what is seen in other population studies. 19 , 22 , 23 The typical value of V (65 L) was comparable to previously reported values. 18 , 22 , 24 During the covariate selection process, the OFV value decreased by 50.22 points (p>0.001) when CLcr was added to the model.…”
Section: Discussionsupporting
confidence: 90%
“… 19 , 22 , 23 The typical value of V (65 L) was comparable to previously reported values. 18 , 22 , 24 During the covariate selection process, the OFV value decreased by 50.22 points (p>0.001) when CLcr was added to the model. Previous studies have reported serum creatinine CLcr as an important covariate explaining BSV in vancomycin’s CL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In actual practice, conditional WRES is usually with FOCE-I, and of course this is acceptable. Thus, conditional WRES are all with FOCE-I in the following: Jing et al’s ( 2021 ) pharmacokinetic analysis and dosing guidelines for tacrolimus co-administration with wuzhi capsules in Chinese renal transplant recipients; Li et al’s (2021 ) study of dose tailoring of tacrolimus, based on a non-linear pharmacokinetic model in children with refractory nephrotic syndrome; Yu et al’s (2021 ) study of pharmacokinetics and optimization of polymyxin B dosing in adult patients with various renal functions; Ma et al’s (2020 ) study of the pharmacokinetics of vancomycin in kidney transplant recipients; and Cai et al’s (2020 )model building and parameter optimization in pharmacokinetics and dosing regimen optimization of tacrolimus in Chinese lung transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines recommend dosing strategy and monitoring of vancomycin treatment in obese patients in a manner similar to non-obese patients (Durand et al, 2018). Multisite studies have been documented the PK parameters of vancomycin in non-obese patients (Katip et al, 2016;Ma et al, 2020;Arjangpour et al, 2022). However, the data among obese patient is limited.…”
Section: Introductionmentioning
confidence: 99%